A Systematic Approach Towards Web Preservation. - Khan, Muzammil; Rahman, Arif Ur (Information Technology & Libraries, 2019)
The main purpose of the article is to divide the web preservation process into small explicable stages and design a step-by-step web preservation process that leads to creating a well-organized web archive. A number of research articles are studied about web preservation projects and web archives, and designed a step-by-step systematic approach for web preservation. The proposed comprehensive web preservation process describes and combines strengths of different techniques observed during the study for preserving digital web contents into a digital web archive. For each web preservation step, different approaches and possible implementation techniques have been identified that can be adopted in digital archiving. The potential value of the proposed model is to guide the archivist, related personnel, and organizations to effectively preserved their intellectual digital contents for future use. Moreover, the model can help to initiate a web preservation process and create a wellorganized web archive to efficiently manage the archived web contents. A section briefly describes the implementation of the proposed approach in a digital news stories preservation framework for archiving news published online from different sources.